2019
DOI: 10.1186/s41983-019-0068-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in acute ischemic stroke: relation to initial severity and short-term outcome

Abstract: Background: A growing body of evidence indicated that vitamin D has a potential protective role against neurovascular injury. Low serum vitamin D has been associated with increased risk for incident stroke and stroke fatality.Objective: This study aimed to investigate vitamin D status among acute ischemic stroke patients and examine its relation to initial severity and short-term outcome. Subjects and methods: Forty-eight acute ischemic stroke patients and 48 matched healthy control subjects participated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…In this study, the results of multivariable logistic regression analysis showed that after controlling other risk factors, age, dyslipidemia, vitamin D deficiency, and large infarction size were statistically significant independent factors associated with stroke severity. This was in agreement with other studies which showed that vitamin D deficiency was associated with stroke severity [25,33] Regarding stroke outcome, multivariable logistic regression analysis showed that high NIHSS score, vitamin D deficiency, and large infarction size were significantly associated with mRS. Our result was in accordance with the result of other studies demonstrated that vitamin D level is a good biomarker for prognosis, functional outcome, and death in patients with acute ischemic and hemorrhagic stroke [25,26,33,34]. This could be explained by the neuroprotection role of vitamin D via activation of detoxification pathways, upregulation of antioxidation/anti-inflammatory mechanisms, inhibition of inducible nitric oxide synthase, and regulation of neuronal calcium metabolism [35,36].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the results of multivariable logistic regression analysis showed that after controlling other risk factors, age, dyslipidemia, vitamin D deficiency, and large infarction size were statistically significant independent factors associated with stroke severity. This was in agreement with other studies which showed that vitamin D deficiency was associated with stroke severity [25,33] Regarding stroke outcome, multivariable logistic regression analysis showed that high NIHSS score, vitamin D deficiency, and large infarction size were significantly associated with mRS. Our result was in accordance with the result of other studies demonstrated that vitamin D level is a good biomarker for prognosis, functional outcome, and death in patients with acute ischemic and hemorrhagic stroke [25,26,33,34]. This could be explained by the neuroprotection role of vitamin D via activation of detoxification pathways, upregulation of antioxidation/anti-inflammatory mechanisms, inhibition of inducible nitric oxide synthase, and regulation of neuronal calcium metabolism [35,36].…”
Section: Discussionsupporting
confidence: 93%
“…These results were in agreement with the results obtained by other studies [23][24][25][26]. The association of vitamin D deficiency with stroke severity and outcome after controlling for other risk factors suggests a role for vitamin D in the pathogenesis of [27,28].…”
Section: Discussionsupporting
confidence: 92%
“…It is due to the higher intake of vitamin D in the case group compared to the control group. Respondents with insufficient vitamin D were revealed to have a 2.88 times higher risk of stroke than those with appropriate levels, and this risk increased to 13.78 times higher in respondents who were deficient in vitamin D compared to those in the moderate category (Fahmy et al, 2019). The findings of this study indicate that the incidence of vitamin D deficiency and the incidence of stroke influence each other.…”
Section: Relationship Of Vitamin D Intake With Stroke Incidencementioning
confidence: 57%
“…The results illustrated that insufficient vitamin D intake (40% of respondents) was associated with the incidence of stroke (p 0.016). It is reinforced by previous research which states that vitamin D deficiency has a relationship with the incidence of ischemic stroke (Chaudhuri et al, 2014;Fahmy et al, 2019;Talebi et al, 2020). Higher infarct volume is independently associated with lower serum 25(OH)D (blood vitamin D levels) levels in stroke patients (Huang et al, 2016;Nie et al, 2017;Turetsky et al, 2015;Wang et al, 2014).…”
Section: Relationship Of Vitamin D Intake With Stroke Incidencementioning
confidence: 80%
“…A prospective cohort study, conducted in China, showed that vitamin D deficient patients were at a higher risk of exhibiting post-stroke cognitive impairment than those with vitamin D insufficient and vitamin D sufficient patients [ 14 ]. Fahmy et al concluded that the likelihood of stroke increased > 13 times in a vitamin deficient patient [ 15 ]. Neuroimaging of patients with low 25-hydroxycholecalciferol revealed lacunes, severe white matter hyperintensity, and cerebral microbleeds in basal ganglia, thalamus, and brain stem, suggesting that chronic brain injury was associated with small vessel disease [ 16 ].…”
Section: Introductionmentioning
confidence: 99%